The Other Welfare : Supplemental Security Income and U.S. Social Policy - Berkowitz, Edward D.; DeWitt, Larry, 1949- (Book collections on Project MUSE., 2013)
'The Other Welfare' offers the first comprehensive history of Supplemental Security Income (SSI), from its origins as part of President Nixon's daring social reform efforts to its pivotal role in the politics of the Clinton administration. Enacted into law in 1972, Supplemental Security Income (SSI) marked the culmination of liberal social and economic policies that began during the New Deal. The new program provided cash benefits to needy elderly, blind, and disabled individuals. Because of the complex character of SSI - marking both the high tide of the Great Society and the beginning of the retrenchment of the welfare state - it provides the perfect subject for assessing the development of the American state in the late twentieth century. SSI was launched with the hope of freeing welfare programs from social and political stigma ; it instead became a source of controversy almost from its very start. Intended as a program that paid uniform benefits across the nation, it ended up replicating many of the state-by-state differences that characterized the American welfare state. Begun as a program intended to provide income for the elderly, SSI evolved into a program that served people with disabilities, becoming a primary source of financial aid for the de-institutionalized mentally ill and a principal support for children with disabilities. Written by a leading historian of America's welfare state and the former chief historian of the Social Security Administration, 'The Other Welfare' illuminates the course of modern social policy. Using documents previously unavailable to researchers, the authors delve into SSI's transformation from the idealistic intentions of its founders to the realities of its performance in America's highly splintered political system. In telling this important and overlooked history, this book alters the conventional wisdom about the development of American social welfare policy.